THE INFLUENCE OF TAXPAYER AWARENESS AND TAX SERVICES ON MOTOR VEHICLE TAXPAYER COMPLIANCE AT THE TAKALAR DISTRICT SAMSAT - Yusran, Muh; Akbardin, Muhammad; Noor, Randy Mauna (Journal Of Accounting And Finance, 2026)
This study aims to analyze the influence of taxpayer awareness and tax services on the compliance of motor vehicle taxpayers at the Samsat Office of Takalar Regency. The research method used is quantitative, with data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using multiple linear regression, t-test, and F-test. The results of the study indicate that taxpayer awareness and tax services have a positive and significant influence, both partially and simultaneously, on taxpayer compliance. Taxpayer awareness is found to be the dominant factor influencing compliance, while tax services also contribute by improving taxpayer satisfaction and facilitating the fulfillment of tax obligations.